2016
DOI: 10.1021/acs.langmuir.6b03149
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the PVP–Pd Surface Interaction in Nanoparticles through the Case Study of Formic Acid Decomposition

Abstract: Palladium nanoparticles (Pd NPs) were synthesised by the reduction-by-solvent method using polyvinylpirrolidone (PVP) as capping agent. The non-static interaction between PVP and the metallic surface may change the properties of the NPs due to the different possible interactions, either through the O or N atoms of the PVP. In order to analyse these effects and their repercussion in their catalytic performance, Pd NPs with various PVP/Pd molar ratios (1, 10 and 20) were prepared, deposited on silica and tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 57 publications
4
46
0
Order By: Relevance
“…Some of the strategies tackled in this matter include the optimization of the active phase features (in terms of size, composition, structure, and so forth) as well as the impact of the support properties in modulating the final behavior of the catalysts by controlling the metal-support interaction or the acid/base properties. There are a number of supports investigated for this application, including silica (García-Aguilar et al, 2016b;Mori et al, 2017a), zeolites (Navlani-García et al, 2015a), metal-organic frameworks (MOFs) (Wen et al, 2017), etc. Among them, carbon materials are certainly the most extensively investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the strategies tackled in this matter include the optimization of the active phase features (in terms of size, composition, structure, and so forth) as well as the impact of the support properties in modulating the final behavior of the catalysts by controlling the metal-support interaction or the acid/base properties. There are a number of supports investigated for this application, including silica (García-Aguilar et al, 2016b;Mori et al, 2017a), zeolites (Navlani-García et al, 2015a), metal-organic frameworks (MOFs) (Wen et al, 2017), etc. Among them, carbon materials are certainly the most extensively investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, microwave-assisted reduction with ethanol generated nanoparticles of similar sizes for all five metals, which is difficult by other methods because of the varying properties of the metals 13), 14) . We also found that the amount of PVP, which is a crucial determinant of catalytic activity 9) , varied over a narrow range (74.1-84.5 wt%). As described later, particle size greatly affects catalytic performance, so consistent particle sizes are important for comparing the intrinsic catalytic activities of various metals.…”
Section: Particle-size Distributions Of Noble-metal Nanoparticles mentioning
confidence: 71%
“…Charge transfer from PVP to Rh occurs easily in nanoparticles stabilized by a large amount of PVP. 15 In the case of small Rh nanoparticles, the fact that large numbers of Rh atoms are in contact with PVP facilitates charge transfer, and thus, more electron-enriched Rh surface is formed. In addition, this charge transfer may induce a peak shift of the XRD pattern to a lower angle ( Figure 1); i.e., charge transfer from PVP to the antibonding e g orbital of Rh may result in expansion of the Rh lattice.…”
Section: +mentioning
confidence: 99%
“…The amount of PVP, a crucial determinant of catalytic activity, varied over a small range (72.384.1 wt %). 15 We discovered that the Rh particle size was dependent on the reduction ability of the alcohol. We also studied the particle size dependence of the CO oxidation ability of the Rh nanoparticles, because Rh is known to be an excellent catalyst for the oxidation of CO in car exhaust gas.…”
mentioning
confidence: 99%